2014
DOI: 10.2337/dc14-0596
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Telephone Outreach to Improve Medication Adherence and Metabolic Control in Adults With Diabetes

Abstract: OBJECTIVEMedication nonadherence is a major obstacle to better control of glucose, blood pressure (BP), and LDL cholesterol in adults with diabetes. Inexpensive effective strategies to increase medication adherence are needed.RESEARCH DESIGN AND METHODSIn a pragmatic randomized trial, we randomly assigned 2,378 adults with diabetes mellitus who had recently been prescribed a new class of medication for treating elevated levels of glycated hemoglobin (A1C) ≥8% (64 mmol/mol), BP ≥140/90 mmHg, or LDL cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 25 publications
0
52
0
2
Order By: Relevance
“…The speed of the glucose-lowering effect using the TeLiPro approach was comparable with that observed after bariatric surgery (25). The number of telemedical approaches for lifestyle alterations and chronic disease self-management programs are increasing and encouraging (26,27), although it has been shown that telephone calls alone are not sufficient to sustainably alter behavior (28). Therefore, the TeLiPro combines different interventions; this multifactorial approach does not allow dissection of the effect of the individual components.…”
Section: Discussionmentioning
confidence: 87%
“…The speed of the glucose-lowering effect using the TeLiPro approach was comparable with that observed after bariatric surgery (25). The number of telemedical approaches for lifestyle alterations and chronic disease self-management programs are increasing and encouraging (26,27), although it has been shown that telephone calls alone are not sufficient to sustainably alter behavior (28). Therefore, the TeLiPro combines different interventions; this multifactorial approach does not allow dissection of the effect of the individual components.…”
Section: Discussionmentioning
confidence: 87%
“…The authors of 34 studies that included adults over a wider age range were contacted, and five replied with study information. The majority of studies (123) were published after 2012 . Five studies were conducted in Europe , five in North America , two in Australia and one in the Western Pacific region .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (123) were published after 2012 . Five studies were conducted in Europe , five in North America , two in Australia and one in the Western Pacific region . Most studies were conducted in type 1 diabetes (eight studies) , three studies included both type 1 and 2 diabetes , and two studies included only type 2 diabetes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized trial of telephone outreach was conducted at four large multispecialty medical groups to improve medication adherence and intermediate outcomes of care. 20 The intervention, which was delivered by pharmacists, diabetes educators, or nurse health managers, failed to significantly improve glucose, BP, or LDL-C control.…”
Section: Discussionmentioning
confidence: 99%